2014
DOI: 10.1177/0003319714537111
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Flavonoid-Rich Fruit and Vegetable Consumption and Total Serum Bilirubin

Abstract: Emerging work demonstrates that serum bilirubin is a novel biomarker implicated in cardiovascular and metabolic diseases. However, we have a limited understanding of the influence of flavonoid-rich fruit and vegetable consumption on bilirubin levels, which was the purpose of this study. Data from the 2003 to 2006 National Health and Nutrition Examination survey were used (n = 1783; 18-85 years of age), with analyses performed in 2014. Total serum bilirubin was measured from a blood sample. Using a food frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
(52 reference statements)
3
13
0
Order By: Relevance
“…32 The high-glucose diet has the same hyperbilirubimemic effect, whereas the low-fat diet acts in the opposite way. 33 The same hyperbilirubinemic effect was recently reported for the intake of flavonoid-rich fruits and vegetables, 34 and it is likely that many other nutrients might have a similar impact (also see below).…”
Section: Lifestyle Factorssupporting
confidence: 63%
“…32 The high-glucose diet has the same hyperbilirubimemic effect, whereas the low-fat diet acts in the opposite way. 33 The same hyperbilirubinemic effect was recently reported for the intake of flavonoid-rich fruits and vegetables, 34 and it is likely that many other nutrients might have a similar impact (also see below).…”
Section: Lifestyle Factorssupporting
confidence: 63%
“…Briefly, participants were asked to report the proportion of time certain types of foods were eaten. For the present study, which is consistent with other studies ( Loprinzi and Mahoney, 2015 , Mahoney and Loprinzi, 2014 ), 15 [solid] fruits and vegetables rich in flavonoids (i.e., apples, grapes, strawberries, oranges, cooked greens, raw greens, carrots, string beans, peas, broccoli, onions, peppers, cucumbers, tomatoes, and lettuce) were identified by using the USDA flavonoid content of foods ( USDA, 2007 ). For each of the 15 food items, response options ranged from 1 to 11, and included never (1), 1–6 times/yr (2), 7–11 times/yr (3), 1 time/month (4), 2–3 times/month (5), 1 time/wk (6), 2 times/wk (7), 3–4 times/wk (8), 5–6 times/wk (9), 1 time/day (10), and 2 or more times/day (11).…”
Section: Introductionsupporting
confidence: 91%
“…The corresponding work showed a decrease in this value for populations who consumed either carbohydrate and calorie-rich foods or diet containing high fat and carbohydrate as compared with the standard normal diet (ρ < 0.001) [1,2]. This same pattern of results was also reported by [3] for frequent caffeine consumers.…”
Section: Introductionsupporting
confidence: 75%
“…In addition to the underlying health status, previous research revealed that one's blood bilirubin concentration would also be affected by the change in their dietary intake [1]. The corresponding work showed a decrease in this value for populations who consumed either carbohydrate and calorie-rich foods or diet containing high fat and carbohydrate as compared with the standard normal diet (ρ < 0.001) [1,2].…”
Section: Introductionmentioning
confidence: 99%